2013
DOI: 10.9790/0837-0723542
|View full text |Cite
|
Sign up to set email alerts
|

How can Dialogue Journal Writing improve learners’ writing performance in the English as a Second Language context?

Abstract: Abstract:This paper compared the effect of two different methods in writing including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…This might be traced back to the three fundamental features of dialogue journal writing, namely the freedom in choosing the content to write about, writing a lot about those interested topics in a stress-free environment, and the dialogic individual feedback by the teacher (Mlynarczyk, 2013). Results of the present study regarding the observed improvement of content in learners' writings are in line with Foroutan et al (2013b), Kose (2005), and Peng (2007) who found a significant effect of dialogue journal writing on the content quality of learners' writing performance. This observed effect in the present study can be discussed with regard to the nature of dialogue journal writing which calls for writing about one's topics of interest.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This might be traced back to the three fundamental features of dialogue journal writing, namely the freedom in choosing the content to write about, writing a lot about those interested topics in a stress-free environment, and the dialogic individual feedback by the teacher (Mlynarczyk, 2013). Results of the present study regarding the observed improvement of content in learners' writings are in line with Foroutan et al (2013b), Kose (2005), and Peng (2007) who found a significant effect of dialogue journal writing on the content quality of learners' writing performance. This observed effect in the present study can be discussed with regard to the nature of dialogue journal writing which calls for writing about one's topics of interest.…”
Section: Discussionsupporting
confidence: 83%
“…In other words, as Larrotta (2008) stated, learners acquire new vocabulary through the practice of dialogue journal writing without even realizing it. This was also supported by Foroutan et al (2013b). The non-significant effect of dialogue journal writing on language use and mechanics is in good agreement with Puengpipattrakul (2009) who found a mismatch between learners' ideas about the positive effect of journal writing on their grammatical accuracy and their actual improvement of the use of grammar as a result of practice in journal writing.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As cited from Brown (2004) Dialogue journal is generally an interactive conversation between a teacher and the students which is written in a notebook frequently (weekly or biweekly) about a topic that interests them both, as a regular practices for the students in writing. The role of the teacher is giving feedbacks and comments on the students' work with correct grammatical forms and structure as a model for the students (Forouton, Noordin & Hamzah, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by writing Dialogue journal frequently, the students' writing proficiencies will improve as they go along the process (Liao & Wong, 2010;Naba'h, 2013;Mehrdad, 2008;Forouton, Noordin & Hamzah, 2013). Through regular practices, dialogue journal can build students' fluency on writing.…”
Section: Introductionmentioning
confidence: 99%